Nonverbal Communication Of Legal Counsel With Defendants In Central Jakarta District Court Room - Widodo, Aan (Technium Social Sciences Journal, 2021)
The purpose of this research is to explain the nonverbal communication of legal counsel with the defendant in the conference room at the central Jakarta District Court. The concepts used were communication in trials and nonverbal communication. The study used a qualitative approach with descriptive research methods. Data is obtained by conducting interviews on the 6 informant, observations on 3 trials and literature studies. The results of this study showed that in the trial, legal counsel communicated with the defendant in an attempt to provide legal aid. One form of communication in legal aid is nonverbal communication. Nonverbal communication of legal counsel with defendants using gesture "eye movement" and "sound Code". A Legal counsel with the defendant agreed nonverbal measures as a strategy for winning perceptions in the trial, which implicates the judge’s "light" penalty.